PENGARUH KETERAMPILAN MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V - Stanislaus W Lumban Batu; Jontra Jusat Pangaribuan; Regina Lumban Gaol; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effect of the teacher’s teaching skills on learning motivation for fifth-grade students on mathematics learning subjects for the introduction of fractions. The research was conducted at SDN 106144 Sei Mencirim in June 2021. The research subjects were 200 students. The research method was a descriptive-quantitative method. The instrument used to collect data was the primary source. Hypothesis testing used a t-test. The results of statistical calculations showed that the effect of teachers’ teaching skills on students’ learning motivation on mathematics learning subject in grade V on the introduction of fraction recognition material was categorized in the high category with an average value of 93.53. Furthermore, the hypothesis testing tcount was 5.685 then adjusted with the ttable to a significant level of 0.5. Therefore, the tcount obtained was higher than the ttable, which is 5.685 ≥ 1.309. It can be concluded that the teachers’ teaching skills had a significant effect on the learning motivation of the fourth-grade students of SDN 106144 Sei Mencirim Sunggal in the academic year 2020/2021 on mathematics learning subject for the introduction of fractions. Thus, the teachers’ teaching skills were appropriated to be used in the learning process, especially to motivate students in learning.